White Gloves, Black Nation : Women, Citizenship, and Political Wayfaring in Haiti - Sanders Johnson, Grace (Book collections on Project MUSE., 2023)
"This transnational history of gender and radical politics during and after the US occupation of Haiti follows a cohort of Haitian women from Haiti through the Caribbean to the United States, Canada, and the Belgian Congo. Grace Sanders Johnson uses this group of women to explore how gender, national, and racial identities were forged among elite and middle class women"--